The emerging problem of linezolid-resistant enterococci. (June 2018) - Bi, Ruru; Qin, Tingting; Fan, Wenting; Ma, Ping; Gu, Bing
Highlights: Focus on epidemiological, microbiological and clinical features of linezolid-resistant enterococci (LRE). Results of linezolid (LNZ) surveillance programmes are detailed. Clonal spread of LRE and susceptibility testing indicate the gravity of LNZ resistance. Distribution of LRE worldwide is reported. Mechanisms of LNZ resistance and sites of LRE infection are described. Abstract: Enterococcus is a significant pathogen in numerous infections, particularly in nosocomial infections, and is thus a great challenge to clinicians. Linezolid (LNZ), an oxazolidinone antibiotic, is an important therapeutic option for infections caused by Gram-positive bacterial pathogens, especially vancomycin-resistant enterococci. A systematic review was performed of the available literature on LNZ-resistant enterococci (LRE) to characterise these infections with respect to epidemiological, microbiological and clinical features. The results validated the potency of LNZ against enterococcal infections, with a sustained susceptibility rate of 99.8% in ZAAPS and 99.2% in LEADER surveillance programmes. Patients with LRE had been predominantly exposed to LNZ prior to isolation of LRE, with a mean treatment duration of 29.8 ± 48.8 days for Enterococcus faecalis and 23.1 ± 21.4 days for Enterococcus faecium . Paradoxically, LRE could also develop in patients without prior LNZ exposure. LNZ resistance was attributed to 23S rRNA (G2576T) mutations (51.2% of E. faecalis and 80.5% of E. faecium ) as well as presence of the cfr gene (4.7% and 4.8%, respectively), which could transfer horizontally among the strains. In addition to the cfr gene, 32 cases of optrA -positive LRE were identified. Further study is required to determine the prevalence of novel resistance genes. The emergence of LRE thus hampers the treatment of such infections, which warrants worldwide surveillance.